The last player in football: are match preparedness and compensation an issue for goalkeepers? - Rocha, J.; Vieira, R.; Fino, M.; Menezes, P.; Otte, F.; Silva, H. (Trends in Sport Sciences, 2025)
Introduction: During matches and training sessions, football players are exposed to different demands, which are commonly monitored to ensure that the players are prepared to cope with competition and to avoid excessive fatigue. Unfortunately, goalkeepers are often excluded from these analyses.